Process Innovation Capabilities and Organizational Performance: Case Study of Developing Novel Production Process. (Global Business Management Review (GBMR), 2022)
This case study has been conducted for the purpose of examining the innovative abilities of internal research and development. An empirical technological procedure advancement analysis has been introduced that concentrates on the issues encountered the business sectors of a Saudi firm and the performance of organizational performance. What is revealed in this case study is that the abilities of process Innovation have an important positive impact upon the organization. Lastly, the empirical study has been given including discussions and conclusions. The study provides insight into Process Innovation Capabilities and Organizational Performance, in a self-governing organization in Riyadh, Saudi Arabia.